Sacituzumab govitecan: past, present and future of a new antibody-drug conjugate and future horizon: drug evaluation - Furlanetto, Jenny; Marmé, Frederik; Loibl, Sibylle (Future oncology, 2022)
Sacituzumab govitecan (SG) is a new antibody-drug conjugate directed against the cell-surface antigen Trop-2. Characteristics of the linker connecting the payload SN-38 to the antibody allows SG to kill tumor cells expressing Trop-2 and also the adjacent tumor cells (bystander effect). SG showed efficacy and safety in several epithelial tumors. The phase III ASCENT trial led to the approval of SG (10 mg/kg, d1,8 q3w) in patients with advanced or metastatic triple-negative breast cancer (TNBC) who have received ≥2 prior systemic therapies, including ≥1 for metastatic disease. The phase III TROPiCS-02 trial in heavily pretreated advanced hormone receptor (HR)-positive breast cancer has recently shown an improvement in progression-free survival for patients treated with SG compared to single-agent chemotherapy. The phase III post-neoadjuvant SASCIA study in early high-risk TNBC and HR-positive breast cancer is currently recruiting patients.
Gesehen am 19.09.2023